Ensuring telecommunication network security through cryptology: a case of 4G and 5G LTE cellular network providers - Adnan Manasreh; Ahmed A. M. Sharadqh; Jawdat S. Alkasassbeh; Aws Al-Qaisi (Institute of Advanced Engineering and Science, 2019)
This paper aims to present the details regarding telecommunication network security through cryptology protocols. The data was based on scientific data collection and the quantitative method was adopted. The questionnaire was developed and the primary respondents were approached who were working in 4 telecommunication networking companies namely Huawei, Ericsson, SK Telecom and Telefonica. The sample size of the research was 60 participants and the statistical analysis was used to analyze research. The finding shows that cryptology protocol such as SSH, SSL, Kerberos PGP and SET are implemented within the companies in order to secure network.